The Impact of the Covid 19 Pandemic on Retail Performance at the Sampoerna Retail Community in Soloraya: The Impact of the Covid 19 Pandemic on Retail Performance at the Sampoerna Retail Community in Soloraya - Sajiwo Tri Prakoso (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2022)
Urban communities are now spoiled by the presence of various shopping centers. Even the location is sometimes in one area. This condition is very beneficial because people just have to choose which outlets to enter. Retail is an important link in the distribution process of goods and is the last link in a distribution process. Through retail, a product can meet directly with its users. To stimulate the economy, a supporting program is needed, namely the Sampoerna Ritail Community. Data was collected through a survey with a total of 62 SRCs in Soloraya. This research uses purposive sampling. Data analysis used regression analysis. The results of this study indicate that well being and the use of technology have an influence on retail performance while brand and customer protection, supply chain and government policies have no influence on retail performance